Uji Efektivitas Cendawan Metarhizium anisopliae Terhadap Daya Bunuh Instar 2 Dan Instar 4 Larva Ulat Spodoptera Litura Pada Tanaman Sawi Hijau (Brassica juncea L.) Di Laboratorium - One May Sunday Nababan; Sartini Sartini; Riyanto Riyanto (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2020)
Pests are one of the factors that reduce the production and quality of cultivated plants, for example grayak caterpillars (Spodoptera litura) which attack mustard plants. Grayak caterpillars (Spodoptera litura) can be controlled using chemical compounds (insecticides), can be manually collected by hand and can also be biologically controlled, for example with mushrooms. The purpose of this study was to examine the effectiveness of the fungus Metarhizium anisopliae on Spodoptera litura caterpillar larvae in green mustard plants (Brassica juncea L.). The caterpillar used in this study is the Instar-2 (I₁) and Instar-4 (I₂) phase caterpillars. The concentration of fungi was inoculated were 10-2 (M₁), 10 -4 (M₂), and 10 -6 (M₃), and without fungi as a control (M₀). The design used was Factorial RAL with 3 replications. The experimental results showed that spore density M₁, M₂, and M₃ were quite effective at killing the caterpillar both on instar-2 (I₁) and on instar-4 (I₂